PENGARUH AKSESIBILITAS, KOMUNIKASI, LINGKUNGAN, DAN PELAYANAN TERHADAP PREFERENSI GENERASI MILENIAL BERKUNJUNG KE DESTINASI WISATA HALAL DI JAWA BARAT - Atina Fahma Rosyada (2023)
Weak tourism product development innovation and decreased interest in visiting tourists are becoming a problem for halal tourism in West Java Province. The purpose of this study was to analyze the effect of accessibility, communication, environment, and service on the preferences of millennial generation tourists in West Java. Accessibility includes easy access to a tourist destination, either through land, air or sea transportation. Communication involves effective and easy communication between tourists and related parties, including information about tourist destinations and services offered. The environment includes a safe, clean and comfortable environment for Muslim tourists, including an environment that is free of alcohol. Services include Muslim-friendly services, including halal restaurants and easily accessible places of worship. This research uses descriptive research with a quantitative approach. Sources and data collection techniques are by distributing questionnaires to 141 respondents. The data obtained were then analyzed using Partial Least Square with Smartpls software. The results of this study indicate that accessibility and service have no effect on tourist preferences, while communication and the environment have an effect on tourist preferences.